Efficacy and toxicity studies of Oxytetracycline-loaded calcium carbonate nanoparticles in Corynebacterium pseudotuberculosis infected BALB/c Mice - Idris, Sherifat Banke; Abdul Kadir, Arifah; Abdullah, Faez Firdaus Jesse; Ramanoon, Siti Zubaidah; Abdul Basit, Muhammad; Abubakar, Muhammad Zuki Zackariah (Arak university of Medical Sciences, 2022)
Background: Caseous Lymphadenitis (CLA) is an important bacterial disease in goats, caused by Corynebacterium pseudotuberculosis. The disease is highly prevalent worldwide and causes significant economic losses to the cattle industry. Currently, the treatment of this disease with antibiotics remains largely unsuccessful due to the nature of the bacteria and the resultant resistance to the drugs. Methods: Thirty apparently healthy female BALB/c mice, aged 5-6 weeks old were used to assess the efficacy of oxytetracycline loaded in calcium carbonate nanoparticle (OTC-CSCaCO3NP) and toxicity of calcium carbonate nanoparticle (CS-CaCO3NP). The mice were randomly divided into five groups of six each and were exposed to the following treatments: Group 1: received sterile distilled water; Group 2: received 0.2 ml C. pseudotuberculosis; Group 3: received 0.2 ml C. pseudotuberculosis and 10mg/kg OTC; Group 4: was given 0.2 ml C. pseudotuberculosis and 10mg/kg OTC-CS-CaCO3NP; and Group 5: was administered 20mg/kg CS-CaCO3NP. Results: The clinical signs of infection with C. pseudotuberculosis in the mice were significantly reduced after treatment with OTC-CS-CaCO3NP. The haematology results showed an insignificant reduction in the mean RBC count, Hb and haematocrit levels in Group 2 (infected controls) compared to the mice treated with oxytetracycline loaded nanoparticles. The biochemical analyses revealed no significant changes among the treatment groups. No histopathological lesions were found in the organs of the mice, treated with 20mg/kg CS-CaCO3NP, suggesting the absence of toxicity in vivo. Conclusion: The results from this study indicate the potentials of OTC-CS-CaCO3NP as becoming a nano-antibiotic formulation for the treatment of caseous lymphadenitis infection in mice.